Regulating public services : bridging the gap between theory and practice - Auriol, Emmanuelle; Crampes, Claude; Estache, Antonio (Cambridge : Cambridge University Press, 2021)
Regulation is one of the tools used by governments to control monopolistic behaviour in the provision of public services such as electricity, transport or water. Technological and financial innovations have changed these public services markets since the 1990s, bringing new regulatory challenges, including technological and financial ones. This book demonstrates that basic regulatory theory and tools can address these new challenges, in addition to more traditional regulatory issues, both in developed and developing economies. The theory covered in the book is robust enough to guide regulators in multiple contexts, including those resulting from the effects of financial or political constraints, evolving market structures or the need to adapt to institutional weaknesses, climate change and poverty concerns that demand regulatory intervention. A bridge between theory and an evolving global practice, this book mobilizes the lessons of the past to analyse the future of economic regulation.
Title from publisher's bibliographic system (viewed on 27 Jan 2022).
Keywords: Public utilities -- Government policy; Antitrust law